Family Experiences, Needs, and Perceptions in Home-Based Hospice Care for Patients With Terminal Cancer: Meta-Synthesis and Systematic Review - Xin Ming Deng; Kanokwan Hounsri; Violeta Lopez; Wilson Wai-San Tam (JMIR Cancer)
Abstract BackgroundHome-based hospice care offers patients with terminal cancer the comfort of receiving care in a familiar environment while enabling family members to provide personalised support. Despite the critical role families play, the literature remains underexplored in terms of their experiences, needs, and perceptions. A robust qualitative synthesis is needed to inform improvements in palliative care services. ObjectiveThis meta-synthesis aims to systematically review and synthesize qualitative evidence regarding the experiences, needs, and perceptions of family caregivers in home-based hospice care for patients with terminal cancer. The goal is identifying key themes that can improve caregiver support and service delivery. MethodsA systematic search was conducted across MEDLINE, Embase, Scopus, PsycINFO, CINAHL, Google Scholar, and relevant gray literature sources up to March 14, 2025. Studies were included if they focused on family caregivers’ experiences in home-based hospice care settings, excluding those that addressed only patients or health care providers. Two independent reviewers performed study selection, data extraction, and quality assessment using the Critical Appraisal Skills Programme checklist. Data were synthesized using a 3-step thematic synthesis approach, and the confidence in the findings was assessed via the GRADE-CERQual (Grading of Recommendations Assessment, Development, and Evaluation–Confidence in the Evidence from Reviews of Qualitative Research) framework. ResultsFive studies published between 1989 and 2022 from diverse geographical regions (including Asia and Western settings) met the inclusion criteria. Two major themes emerged: (1) being physically and emotionally present, where caregivers expressed a strong commitment to remain with their loved ones, providing emotional support and maintaining a sense of control; and (2) sharing responsibilities, which underscored the importance of both formal support from palliative care teams and informal support from family and friends in mitigating caregiver burden. These findings directly address the study’s aims by illustrating how caregivers balance emotional commitment with the practical challenges of providing home-based care. ConclusionsAlthough family caregivers are dedicated to delivering high-quality, personalized care, they encounter significant emotional and logistical challenges. Variability in study settings, potential recall bias from retrospective interviews, and limited gray literature access may affect the generalizability of the findings. This meta-synthesis underscores the essential role of family involvement in home-based hospice care for patients with terminal cancer. The combined reliance on emotional commitment and shared responsibilities—with support from professional care teams—is vital for optimal care delivery. Future interventions should enhance formal and informal support systems to meet family caregivers’ diverse needs better.